Feasibility study of logging-while-drilling boundary detection using electric dipole antenna - Fan, Changhong; Xiao, Zhanshan; Hu, Haitao; Deng, Shaogui; Fan, Yiren; Qi, Chao; Liu, Gang (Frontiers in Earth Science, 2025)
The critical need for deep boundary detection in complex hydrocarbon reservoirs drives the advancement of Logging-while-drilling (LWD) azimuthal electromagnetic measurement (AEM). New deep detection tools employ open-loop half-circle electric dipole (ED) antennas that enable longer-distance detection compared to traditional closed-loop magnetic dipole (MD) antennas, owing to the unique advantages of electric field signals in azimuthal resolution and amplitude attenuation. However, a significant research gap remains as the reception efficiency of ED antennas is largely unaccounted for. Existing theoretical analyses simplistically assume 100% efficiency, identical to closed-loop MD antennas. In reality, the actual reception efficiency of ED antennas may cause signal attenuation in new deep detection tools, which could compromise boundary identification accuracy and pose a risk to real-time geosteering. To address this issue, this paper investigates the feasibility of boundary detection using ED antennas in LWD by developing a comprehensive framework that integrates antenna characterization, reception efficiency simulation, and depth of detection (DOD) evaluation. The research first compares the attenuation characteristics and resistivity response of ED and MD antennas in homogeneous media. It then reveals the influence mechanisms governing ED antenna reception efficiency, identifying formation resistivity as the dominant factor while demonstrating the negligible effects of operating frequency and relative permittivity in typical low-frequency applications. Furthermore, comparative analysis in single-boundary formations confirms that the new deep detection tool exhibits significantly superior azimuthal sensitivity and a DOD exceeding twice that of traditional tools, even when efficiency attenuation is accounted for. This work provides the theoretical and empirical evidence necessary to validate ED antennas for reliable deep boundary detection, enhancing the safety and accuracy of geosteering in complex environments.